SYNERGIES FROM MERGERS AND ACQUISITIONS: CASE STUDIES - Alexander, Joby (2006)
Despite the seemingly high risks attached, Mergers and Acquisitions (M&A) have been around for almost a century and have been used as an important tool in the growth strategy of a company. Empirical evidence on the creation of value through M&A activity has shown diverse results. Drawing upon this framework, this dissertation aims to identify whether value has been created or destroyed by undertaking merger activity.